Picosecond dynamics of a shock-driven displacive phase transformation in Zr - Swinburne, T; Glavicic, M; Rahman, K; Jones, N; Coakley, J; Eakins, D; White, T; Tong, V; Milathianaki, D; Williams, G; Rugg, D; Sutton, A; et al. (American Physical Society, 2016)
High-pressure solid-state transformations at high strain rates are usually observed after the fact, either during static holding or after unloading, or inferred from interferometry measurements of the sample surface. The emergence of femtosecond x-ray diffraction techniques provides insight into the dynamics of short-time-scale events such as shocks. We report laser pump-probe experiments of the response of Zr to laser-driven shocks over the first few nanoseconds of the shock event, enabling the α→ω transition and orientation relationship to be observed in real time with picosecond resolution. A clear orientation relationship of (101¯10)α||(101¯1)ω is found, in conflict with ω→α annealing experiments in zirconium and the two α→ω pathways proposed for titanium.